EFFECTIVENESS OF AVERRHOA BILIMBI L. LEAF EXTRACT ON TOTAL LEUKOCYTES, LYMPHOCYTES, AND MONOCITES OF FREE-RANGE CHICKEN - Moenek, Devi Yasintha Joice Aprianti; Toelle, Novianti Neliyani; Jacob, Jois Moriani (Buletin Veteriner Udayana, 2023)
Star fruit leaves contain the active compound tannin. Tannin extracts in star fruit leaves have effectiveness as antibacterials and may also have anthelmintic activity. The utilization of belimbing wuluh leaves as a traditional medicine is beneficial to reduce the use of synthetic antibiotics that have a negative impact on native chickens, which cause resistance and residues for consumers. Blood picture is one of the parameters of animal health status because blood has an important function in the physiological regulation of the body. This study aims to determine the total leukocytes, lymphocytes, and monocytes in Gallus domesticus with Averrhoa bilimbi leaf extract treatment. The research was conducted from April-November 2023. A total of 200 grams of Averrhoa bilimbi leaf powder was dissolved with 1,400 mL aqua Proinjection. Then continued with evaporation to produce concentrated extracts and treatment using concentrations; P1: 25%, P2: 30%, and P3: 35% of the extract. The study with 5 treatments and 5 replicates was administered by daily feeding with a duration of 21 days. Blood samples were examined at the Animal Health Laboratory, Department of Animal Husbandry, Politani Negeri Kupang using the Hematology Analyzer VH-22 Labomec Inc. Data analysis using Analysis of Variance (ANOVA), if there are real differences then proceed with the Duncan Test. It can be concluded that the use of star fruit leaf extract concentrations of 25%, 30%, and 35% increases the total value of leukocytes and monocytes, while the value of lymphocytes is below normal values. The best and most effective is at 25% concentration. It is hoped that further research will be carried out on chickens of the same age and body weight so that the pharmacokinetic effects can be seen.